2015
DOI: 10.1186/s12882-015-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of frailty with endothelial dysfunction and its possible impact on negative outcomes in Brazilian predialysis patients with chronic kidney disease

Abstract: BackgroundFrailty is a state of physiological vulnerability common in the elderly. It is more predominant in patients with Chronic Kidney Disease in comparison to healthy subjects, which can also be diagnosed in non-elderly individuals and be associated with innumerous causes such as muscle strength, body composition and inflammation. The association between frailty and endothelial function, as well as the association between frailty and the combined outcome of mortality multiple cause and start of renal repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…Up until recently, the reason why frailty was associated with adverse clinical outcomes has been unclear. Subjects with frailty tended to have endothelial dysfunction ( 32 ) and inflammation ( 33 ). These subclinical pathophysiologic disturbances may explain the intimate association between frailty and various comorbidities, such as diabetes and cardiovascular diseases ( 10 11 23 24 27 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up until recently, the reason why frailty was associated with adverse clinical outcomes has been unclear. Subjects with frailty tended to have endothelial dysfunction ( 32 ) and inflammation ( 33 ). These subclinical pathophysiologic disturbances may explain the intimate association between frailty and various comorbidities, such as diabetes and cardiovascular diseases ( 10 11 23 24 27 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 articles cited here, eight measured frailty using the CHS criteria. [59][60][61][62][63] Some of these studies found that frail CKD patients had significantly lower physical and mental component scores on the Short Form-36 Health Survey than non-frail CKD patients. CKD was associated with increased frailty or reduced physical function (OR 1.30-3.12).…”
Section: Explanationmentioning
confidence: 99%
“…Walker et al carried out a systematic review of cohort studies and observational studies that examined how frailty impacts CKD outcomes. [59][60][61] Two of the studies reported that frailty in CKD patients was associated with increased likelihood of mortality or dialysis therapy (OR 2.0-2.5). In patients with CKD, frailty was associated with a greater likelihood of dialysis and death (OR 2.00-5.88).…”
Section: Explanationmentioning
confidence: 99%
See 2 more Smart Citations